Electrical Energy Audit of Operation Support Equipment at 200 MW Steam Power Plant - Heri Priagusno; Surya Hardi; Rohana Rohana; Arnawan Hasibuan; Muzamir Isa (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
Based on data from the Pangkalan Susu steam power plant, the total amount of electrical energy used for generating process is on average 10% by the total of electrical energy generated by the plant. Increasing of electrical energy used will reduce the electrical energy sales to the network system. This research was carried out with reference according to ISO 50006:2014. This research is studies to the sample equipment with the largest rating capacity (significant energy user), such as boiler and turbine operation support equipment with on voltage 6 kV. The data of electrical energy in equipment is taken from the last 3 years historical data, namely in 2020, 2021 and 2022, Furthermore, the lowest point of electrical energy usage data was selected, then analyzed with the Linear Regression method to obtain the baseline Energy equation. The equation is used to conduct an analysis by comparing against the new data of the electrical energy in equipment, namely on April 1, 2023, the analysis showed that there was a waste of electrical energy of 164.12 kW equivalent to a fuel purchase loss of IDR 2,343,960 in 1 day. Furthermore, the baseline equation is used to input formulas in the AVEVA application (PI VISION). The Changes of electrical energy used will be monitored directly, so that if there is a waste of electrical energy, the operating pattern can be regulated directly to avoid energy waste in the electrical equipment and earn the fuel cost reduction of the Steam Power Plant.